Are Primetime Diets Congruent With Dietary Recommendations? Content Analyses of Food Advertisements in the United States, China, and Singapore. (1st January 2016) - Yeo, Su Lin; Shin, Wonsun; Lwin, May; Williams, Jerome; Hong, Ying-Yi
Abstract : Despite public programs to promote healthy eating among populations in developed and developing countries, the increase in obesity as a result of poor dietary patterns continues to persist. As food advertising has been implicated for contributing to this global health challenge, this study aims to provide empirical evidence on food advertising in a broader global context, across economically and culturally different nations. We conducted a large scale content analysis of the types of food advertised on primetime television in the United States, China, and Singapore, which resulted in the collection of 1, 008 television hours. Using the dietary blue2376s proposed by the health authorities as the applied framework, the study compared the types of food advertised against the dietary parameters. Findings showed that despite differences in economic development and cultures, food advertised on primetime television across three countries are incongruent with dietary recommendations. The study offers insights on how misaligned and out of sync food advertising and commercial interests are from government health policies. Implications of findings to encourage healthy eating among populations worldwide are discussed.